Pengaruh Produk Domestik Regional Bruto (PDRB) Dan Tingkat Upah Terhadap Kesempatan Kerja Melalui Investasi Di Provinsi Bali Tahun 1993-2013 - Permana, I Gusti Agung Bagus Ari Surya; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
The development of employment opportunities in the province of Bali in 2013 has decreased , the high number of labor force and the limited employment opportunities is an important issue that can lead to increased unemployment in Bali This study aims to determine how the influence GDP, investment, and the level of wages on employment in the province of Bali. Samples taken are Bali in Figures annual report for 20 periods of the GDP, Investment, Wages and Employment Story, namely the period 1993 -2013. The data analysis technique used is the technique of path analysis (path analysis). The test results showed that the GDP effect on investment in the province of Bali. GDP, Investment and Wage Levels effect on employment. In addition, there is an indirect effect of GDP on employment in the province of Bali through investments or investments in other words a mediating variable in the GDP effect on Employment in the province of Bali.
Keywords: GDP; investment; wages; employment opportunities